Innovative maritime logistics in achieving higher flexibility and resilience : a two-stage QFD approach to improve maritime supply chain resilience - Du, Ye (2015)
Maritime logistics providers face a volatile environment characterized by uncertainty and risks imposed by supply chain and their own actions. Using liner companies as representative of maritime service providers, this paper aims to find innovative measures to increase the resilience.